Open hand vs. half-crimp: Do climbers assume differences in their own maximal finger strength that do not exist? - Carla Zihlmann; Paul Ritsche; Andri Feldmann; Lisa Reissner; Martin Keller; Peter Wolf (Current Issues in Sport Science)
Many climbers believe that they are stronger in crimp finger position than in open hand position. However, the crimp grip is associated with higher pulley forces, increasing the risk of finger injuries. If a climber turns out not to be stronger in crimp than in open hand position - as they might have assumed - the open hand grip, which is easier on the pulleys, should be used whenever possible. Therefore, this study aimed to determine how accurate climbers could assess their maximal finger flexor strength in half-crimp and open hand positions. We assumed that the accuracy of self-assessment increases with skill level. Finger strength data along with self-assessment questionnaires were collected from 38 intermediate, 36 advanced climbers and 11 elite athletes. Our results revealed that advanced climbers significantly overestimated their strength in the half-crimp position compared to the open hand on average by 9.8% for the non-dominant hand. Such an overestimation, albeit not significant, was also found among intermediate and elite climbers (5.6% and 6.3%). The inaccurate estimate may be because we did not explicitly inform participants that they would be tested on a 23mm deep rung where they could place their entire distal phalanx. The crimp position might be stronger than the open hand position on less deep rungs - supporting their estimation. No significant differences in self-assessment accuracy were observed between groups. Thus, we cannot conclude that higher skilled climbers assess their strength capacities more accurately. For all skill levels and both sexes, slightly higher forces in open hand than in half-crimp position were found. Hence, we confirm that for deeper hold depths, using an open hand position has no force disadvantage when compared to the half-crimp. Accordingly, we recommend adopting an open hand position on rungs on which almost the entire distal phalanx can be placed.